Cancers professionnels - Julie Primerano; Anne Marchand (La Nouvelle Revue du Travail)
Nearly two-thirds of employees exposed to carcinogenic substances at work are blue-collar workers. Every year in France, thousands of employees - between 14,000 and 30,000, according to the latest French cancer survey - contract an occupational cancer. Most die. The article describes the results of a field study conducted in Lorraine and Seine-Saint-Denis, two of France’s oldest industrial regions. Employees and ex-employees suffering from work-related cancer were interviewed, along with their families, in order to understand the evaluation, categorisation and assessment processes that they faced from a political and financial perspective. In terms of the reparations they were offered, it becomes clear that workers’ well-being is not a neutral subject. Quite the contrary, their ill health bears witness to (and proves) the unhealthy situations to which they were exposed on the job. That being the case, health can be construed here a medical object capable of being apprehended through social filters – a reflection of domination relationships, hence a rationalised construct subject to fractal monetisation.